2017
DOI: 10.1007/s00445-017-1111-2
|View full text |Cite
|
Sign up to set email alerts
|

Contrasting origin of two clay-rich debris flows at Cayambe Volcanic Complex, Ecuador

Abstract: International audienc

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 33 publications
0
14
0
Order By: Relevance
“…Cronin et al ., ; Detienne et al ., ). It is important to identify hydrothermal minerals formed under near surface, supergene or hypogene hydrothermal environments (John et al ., ; Detienne et al ., ), as well as sulphidation states such as high sulphidation in the central part of a volcano or low sulphidation more distally (Hedenquist & Lowenstern, ), and whether they are linked to vertical and lateral distributions sampled by: (i) a surface landslide; (ii) a deeper collapse; and/or (iii) a phreatic (hydrothermal) eruption without collapses (John et al ., ; Sillitoe, ; Detienne et al ., ). The XRD results (Table ) indicate that the both Gm/Gs and Bm/Bs deposits have a variety of clay mineralogy derived from hydrothermally altered rocks (details discussed below) suggesting a different source.…”
Section: Eruptive Styles and Lahar Trigger Revealed By Event Depositsmentioning
confidence: 97%
“…Cronin et al ., ; Detienne et al ., ). It is important to identify hydrothermal minerals formed under near surface, supergene or hypogene hydrothermal environments (John et al ., ; Detienne et al ., ), as well as sulphidation states such as high sulphidation in the central part of a volcano or low sulphidation more distally (Hedenquist & Lowenstern, ), and whether they are linked to vertical and lateral distributions sampled by: (i) a surface landslide; (ii) a deeper collapse; and/or (iii) a phreatic (hydrothermal) eruption without collapses (John et al ., ; Sillitoe, ; Detienne et al ., ). The XRD results (Table ) indicate that the both Gm/Gs and Bm/Bs deposits have a variety of clay mineralogy derived from hydrothermally altered rocks (details discussed below) suggesting a different source.…”
Section: Eruptive Styles and Lahar Trigger Revealed By Event Depositsmentioning
confidence: 97%
“…3a). This escarpment resulted from a sector collapse most likely caused by hydrothermal alteration that weakened the western flank of Nevado Cayambe edifice during the Late Pleistocene (Detienne et al, 2017). As a result of this event, the steep slopes of the upper Río Blanco valley are characterized by a widespread hydrothermal alteration.…”
Section: Río Blanco Longitudinal Profile (A-a') -East To Westmentioning
confidence: 99%
“…This study focuses on Cayambe Volcano, in the north of the Eastern Cordillera of the Ecuadorian Andes, just 60 km north of the capital Quito. The complex is a notably large volcanic centre, with a peak elevation of 5,790 m. Above 4,800 m the volcano is covered in a 22 km 2 ice cap, which in places is as thick as 100 m (Guillier and Chatelain, 2006;Detienne et al, 2017). Tephrochronology studies have revealed previous explosive activity in the last 4,000 years, including pyroclastic flows, lava dome extrusions and collapse events (Samaniego et al, 1998).…”
Section: Cayambe Volcanomentioning
confidence: 99%
“…Hydrothermal alteration of flank deposits and thawing soils from glacial retreat act to destabilise the western slopes of Cayambe. Small perturbations in the system, for example, from a magmatic intrusion or seismic event, could lead to catastrophic failure and significant landslides (Hoblitt et al, 1998;Detienne et al, 2017). This would pose a threat to the town of Cayambe, population 20,000, that sits just 15 km west of the volcano (Samaniego et al, 1998).…”
Section: Cayambe Volcanomentioning
confidence: 99%